IMPLEMENTASI PERATURAN DAERAH NOMOR 17 TAHUN 2017 TENTANG RETRIBUSI JASA UMUM - Nurhidayati, Nurhidayati; Rahayu, Sri; Jatu Permatasari, Safrieta (JURNAL KATARSIS, 2025)
This analysis discusses the implementation of Regional Regulation Number 17 of 2017 concerning Public Service Retribution, specifically in parking services in Banyuwangi.The main issue lies in the low parking retribution income due to the lack of adequate facilities and infrastructure, as well as suboptimal management.The purpose of this research is to evaluate the effectiveness of the implementation of the policy and identify the obstacles encountered.The methodology used is a qualitative approach with in-depth interviews with key informants, including Transportation Department officers and parking service users.The research results indicate that the limited availability of parking facilities and the lack of official parking attendants contribute to this issue.In addition, ineffective communication between the government and the community also poses a challenge.The conclusion of this research emphasizes the need for improvements in facilities and infrastructure, an increase in the number of parking attendants, and enhancements in communication and socialization of policies to the public.These efforts are expected to increase local revenue and provide better service to parking users.